MUKJIZAT AL-QUR’AN - Sumper Mulia Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
The miracle of the Qur'an, had dragged classical theologians into a contentious debate, especially between Mu'tazilah theologians and Ahlussunnah theologians regarding the concept of shirfah. With a miracle intermediary, Allah SWT reminded people that the apostles were envoys who received support and assistance from the sky. The miracle that has been given to the prophets has the same function, namely playing its role and overcoming the intelligence of its people besides proving that the power of Allah SWT is above all things.